APOE‐e4, microbiota and inflammation in healthy elderly: Inflammation: From basic science to biomarkers. (7th December 2020) - Marizzoni, Moira; Cattaneo, Annamaria; Mirabelli, Peppino; Mombelli, Elisa; Andryszak, Paulina; Nicolosi, Valentina; Roux‐Lombard, Pascale; Salvatore, Marco; Frisoni, Giovanni B.
Abstract: Background: Apolipoprotein E (APOE) ε4 allele is the main genetic risk factor for AD and has different roles in modulating the disease process along with the continuum from intact cognition to dementia due to AD, with its strongest influence at the earliest stages. The aim of this study is to test our hypothesis that places APOEε4 as a trigger in the perturbation of gut microbiota homeostasis. Method: Fecal samples were collected from 28 cognitively intact elderly with known APOE genotype. Bacterial 16S rRNA gene was sequenced according to the 16S‐protocol on MiSeq (Illumina). Taxonomic abundance was computed with the free software package QIIME 2 (Quantitative Insights into Microbial Ecology; Bokulich, Microbiome, 2018; https://qiime2.org/). Plasma levels of cytokines were measured using a commercially available multiplex beads immunoassay, based on the Luminex platform. Result: APOEε4 carriers showed altered abundance in 5 genera (LEfSe, p<0.048), 3 more (Bifidobacterium, Actinomyces, Lactococcus) and 2 less (Ruminococcaceae UCG‐003, Candidatus Melainabacteria) abundant, as well as decreased blood levels of IL‐8 (p=0.047) compared with non‐carriers. Elevated abundance of Bifidobacterium, Actinomyces, Lactococcus were associated with decreased levels of IL‐8 and IL‐6 (rho<‐0.41, p<0.040). Conclusion: Structural microbiota alterations are associated with the restraint of some peripheral pro‐inflammatory signaling pathways in healthy subjects at genetic risk for AD. As a "good" form of inflammation (i.e. I‐6, IL1‐beta, TNF‐alpha) has been proposed to be beneficial in the early phases of the disease in several AD mouse models (Chakrabarty, J Neurosci 2010; Shaftel, J Neurosci 2007), these preliminary data suggest that the deleterious impact of the APOE4 allele on AD development might start in the gut.